Embryonic developmental study of Pink skunk clownfish, Amphiprion perideraion (Bleeker, 1855) - Nakhwa, Mihir; N.B., Dhayanithi; P. R., Divya; T. T., Ajith Kumar; Kumar Sarkar, Uttam (Journal of King Abdulaziz University: Marine Sciences, 2023)
The present study was conducted to document the embryonic developmental stages of clownfish, Amphiprion perideraion in captivity. The water quality parameters such as salinity (30 ppt), pH (8.2), temperature (28 ± 1°C), ammonia and nitrite (below the detectable levels) were standardized and maintained throughout the study period. The newly spawned eggs were adhesive, telolecithal, and white to yellowish-white-colored yolk. The eggs measured around 2.0-2.1 mm in length and 0.9-1.0 mm in width. The chorion was transparent and embryonic developmental stages could be observed directly through the shell. A large clear oil droplet and several smaller droplets were observed. After one hour, blastodisc appeared at the animal pole followed, and various cleavage stages were noted; two, four, eight, sixteen, thirty-two and sixty-four-cells stages, then, morula, blastula, and gastrula were observed. The organogenesis process started after fertilization and later head and notochord formation was evident. The optic vesicles first appeared after 32 hours of fertilization. The turnover stage was passed after 42:10 hours post fertilization (hpf), heart beating and blood circulation started 68:13 hours post fertilization. Lower jaw development started after one hundred twenty-three hours post-fertilization. The embryo reached the pre-hatching stage and hatching was attained after 177 hours of incubation